Polar quantum channel coding with optical multi-qubit entangling gates for capacity-achieving channels - Guo, Ying; Lee, Moon Ho; Zeng, Guihua (Quantum information processing, 2013)
We demonstrate a fashion of quantum channel combining and splitting, called polar quantum channel coding, to generate a quantum bit (qubit) sequence that achieves the symmetric capacity for any given binary input discrete quantum channels. The present capacity is achievable subject to input of arbitrary qubits with equal probability. The polarizing quantum channels can be well-conditioned for quantum error-correction coding, which transmits partially quantum data through some channels at rate one with the symmetric capacity near one but at rate zero through others.